An Examination of Social Solidarity, Value Systems, and Tourism Policy within the Compang Tradition of West Manggarai and the Uma Lengge Tradition of Bima - Haeril, Haeril; Syamsuddin, Syamsuddin; Mas'ud, Mas'ud; Kasman, Kasman; Marfah, Marfah (Universitas Pancasakti, 2025)
This study aims to examine the interrelation between social solidarity, value systems, and tourism policy within the cultural contexts of the Compang tradition in West Manggarai and the Uma Lengge tradition in Bima, by interrogating the extent to which the integration of local cultural practices into tourism contributes to the reinforcement of collective identity or, conversely, to its potential degradation under the hegemony of market logic. Employing a qualitative descriptive approach with a case study design, the research engages indigenous communities in Melo Village (West Manggarai) and Maria Village (Wawo, Bima) as primary subjects, alongside institutional tourism actors, utilizing in-depth interviews, participant observation, and documentation as the principal techniques of data collection. The data were analyzed through qualitative thematic analysis and strengthened by triangulation to ensure validity and reliability. The findings reveal that the Compang and Uma Lengge traditions continue to function as loci of social cohesion, collective identity, and spirituality, yet the intervention of tourism has engendered a transformation of their sacred functions into aesthetic performances, triggering social fragmentation and inequities in the distribution of economic benefits most pronounced in the case of Compang, which is more vulnerable to commodification. In contrast, Uma Lengge demonstrates stronger community participation and relatively fairer benefit distribution, though it still faces the risk of desacralization. The study concludes that the sustainability of cultural tourism can only be secured through policy paradigms that are participatory, equitable, and grounded in substantive cultural recognition, positioning indigenous communities not merely as objects of tourism but as primary agents of social transformation.